2016
DOI: 10.1002/nbm.3679
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural models for diffusion MRI in breast cancer and surrounding stroma: an ex vivo study

Abstract: The diffusion signal in breast tissue has primarily been modelled using apparent diffusion coefficient (ADC), intravoxel incoherent motion (IVIM) and diffusion tensor (DT) models, which may be too simplistic to describe the underlying tissue microstructure. Formalin‐fixed breast cancer samples were scanned using a wide range of gradient strengths, durations, separations and orientations. A variety of one‐ and two‐compartment models were tested to determine which best described the data. Models with restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
0
22
0
2
Order By: Relevance
“…Except for some ex vivo investigations of fixed breast tissues with strong gradients, 37 a previous in vivo study involving 81 patients reported that water diffusion is nearly isotropic in various human breast tumors. 38 Therefore, the DWI signals for IMPULSED acquisitions are obtained by Table 1 lists tissue parameters that can be determined by analyses of DWI data.…”
Section: Diffusion Anisotropymentioning
confidence: 99%
“…Except for some ex vivo investigations of fixed breast tissues with strong gradients, 37 a previous in vivo study involving 81 patients reported that water diffusion is nearly isotropic in various human breast tumors. 38 Therefore, the DWI signals for IMPULSED acquisitions are obtained by Table 1 lists tissue parameters that can be determined by analyses of DWI data.…”
Section: Diffusion Anisotropymentioning
confidence: 99%
“…Recently, VERDICT parameters from ex vivo breast tissue were compared to histology, revealing an association between the intracellular fraction from MRI and the cell fraction from histology. The remaining signal component, assumed to be extracellular, was anisotropic, with directions similar to collagen fibre patterns in the stroma, but fibres were coherent only over distances of 1–2 mm, less than a typical clinical voxel size.…”
Section: Introductionmentioning
confidence: 99%
“…Although extended diffusion protocols and more complex fitting models have proven useful in revealing non-invasive microstructure indices in breast ( 9 ) and prostate ( 10 ), they have not yet been examined in bone metastases. This study explores the potential of microstructure characterization in bone metastases using a rich diffusion protocol with b -values up to 3,000 s/mm 2 and a range of diffusion times, then fitting with a variety of diffusion models.…”
Section: Introductionmentioning
confidence: 99%